Pacific Northwest Plants Record Multiannual Atmosphere–Ocean Circulation Patterns. Issue 19 (4th October 2021) - Stein, Rebekah A.; Sheldon, Nathan D.; Smith, Selena Y.
Abstract: Carbon isotope ecology can be used as a measure of plant water stress. Plant water stress is complicated: multiple factors (e.g., evapotranspiration rates, temperature, precipitation, soil texture, and available water) control the magnitude of the isotopic expression. Often, large ocean–atmosphere pressure systems result in the convergence of constructive climate parameters that result in increased plant water stress; for example, El Niño and Pacific Decadal Oscillation (PDO) anomaly phases. We examined the biogeochemistry of three species ( Thuja plicata : with a Pacific coastal habitat, Thuja occidentalis : native to the Great Lakes region, and Populus tremuloides : a cosmopolitan species found throughout North America). Coincident analyses of these species allowed for intercomparison between plants in habitats directly impacted by atmospheric–oceanic controls on water availability and those out of Pacific impact range. There are oscillatory patterns in the carbon isotope discrimination values (Δ 13 Cleaf ) of Thuja plicata, but no clear patterns in Δ 13 Cleaf values of the other species. We compare the pattern in isotope discrimination of T. plicata with Pacific‐driven multiannual environmental phenomena to determine whether these patterns could be related to the oscillation in Δ 13 Cleaf values. The data demonstrate a regular and significant 14‐ to 19‐year periodicity, aligning most closely with PDO climate patterns. Thuja plicata likely records prolonged stress, like plant available water shortages, which coincide with PDO‐associated shifts in precipitation, humidity, and evapotranspiration. These findings demonstrate that coastal Pacific ecosystems are vulnerable to changes in water availability connected to Pacific teleconnections, providing a new recording tool to examine multiannual climate anomalies. Plain Language Summary: Plants respond to changes in the environment; these changes are recorded in plant chemistry. In this study, we examine how stresses from the Pacific environment, which ultimately control multiple aspects of the environment, affect leaf chemistry of a Pacific coastal tree whose habitat is dominated by Pacific influence. We compare these results to the chemistry of a tree native to the upper Midwest of North America, which is largely uninfluenced by the aspects of Pacific weather and climate, and a tree living throughout North America, with some local specimens influenced by the Pacific, while others too far from the ocean. We find that trees along the coast of the Pacific record anomalies in Pacific air and water conditions, while the other studied trees do not. This is important when we consider how the Pacific Ocean can impact life on land, especially in the context of a warming ocean. Key Points: Carbon isotope values of plants on the Pacific coast record multidecadal Pacific teleconnections Carbon isotope values of plants in the North American interior do not record periodicity associated with Pacific teleconnections These isotope biogeochemistry findings follow prior work linking aboveground terrestrial plants to oceanic–atmospheric teleconnections